General state of mental health in a covid-19 pandemic, in drivers of the supertaxis cooperative “Julio Andrade: General state of mental health in a covid-19 pandemic, in drivers of the supertaxis cooperative “Julio Andrade (La U Investiga, 2021)
Mental health is an essential part of each individual, determined by socioeconomic, biological and environmental factors; associated with continuous social changes, working conditions, especially those that generate work stress, unhealthy and risky lifestyles, as well as inadequate health, among the most important. A descriptive and prospective study was carried out, in which 31 people who worked as active professional drivers of the Supertaxis Cooperative “Julio Andrade” of the Tulcán Canton, Carchi province, Ecuador; during April to October 2020, to characterize the dimensions of the general state of mental health in the COVID-19 pandemic, using the Goldberg GHQ-30 general health questionnaire. It was determined that the factors of social dysfunction (67.7%), insomnia (29%) and somatic symptoms (22.6%) were presented as intermediate and harmful situations, of greater relevance. Similarly, there was a statistically significant relationship between psychosomatic symptoms and working hours (p = 0.009), and with working hours (p = 0.000); in addition to the statistical significance relationship between insomnia and the position held (p = 0.031). It was demonstrated that the psychosomatic symptoms and insomnia were the factors significantly related to the working day and hours, in addition to the position of the worker; assuming therefore that they were therefore related to the greater emotional stress experienced by COVID 19 in the period analyzed.
Keywords: professional drivers; pandemic; COVID 19; mental health